1973
DOI: 10.1111/j.1432-1033.1973.tb02971.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure of Bovine Growth Hormone

Abstract: The study of the structure of the peptides arising from native, oxidized or reduced and maleinized bovine growth hormone on incubation with trypsin, chymotrypsin and pepsin is reported. The data obtained permitted the assembly of a unique sequence of amino acids for the poly‐peptide chain of the protein. Various corrections and one addition to the sequence previously communicated are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…b-STH is a single-chain protein hormone consisting of 191 amino acids. The native structure of rb-STH consists of a four-helix bundle motif with two intrachain disulfide bridges at positions 153/164 and 181/189 (13,14). Physical instability due to perturbation ofthe tertiary structure results in partially unfolded intermediates and potential formation of insoluble aggregates (15).…”
Section: Introductionmentioning
confidence: 99%
“…b-STH is a single-chain protein hormone consisting of 191 amino acids. The native structure of rb-STH consists of a four-helix bundle motif with two intrachain disulfide bridges at positions 153/164 and 181/189 (13,14). Physical instability due to perturbation ofthe tertiary structure results in partially unfolded intermediates and potential formation of insoluble aggregates (15).…”
Section: Introductionmentioning
confidence: 99%
“…Second, there is a relatively hydrophobic stretch of 24 amino acids at the start of this variant region, delineated by an arginine at the end of exon 4 and a glutamic acid at amino acid residue 148, raising the possibility that this polypeptide might be located in a membrane. Third, in wild-type growth hormone, there exists a disulfide bond between cysteine-53 and cysteine-164 (22). Cysteine-164 would be eliminated in a polypeptide derived from the intron D-containing mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid sequences for bSt which differed slightly were published almost simultaneously by Santome et al (1973) and Wallis (1973) . Miller et al (1980) confirmed the Wallis sequence ( Fig.…”
Section: Bst Primary Structurementioning
confidence: 99%
“…Pituitaryderived bSt has been reported to show sequence heterogeneity at the NH zterminus where approximately one-half of the pituitary bSt molecules contain a full-length sequence beginning with Ala-Phe-Pro-Ala-Met-. The other half ofthe molecules begins with Phe-Pro-Ala-Met- (Li and Ash, 1953;Santome et al, 1973;Wallis, 1973). This heterogeneity is likely due to variability in the removal of a prehormone leader sequence (Lingappa et al, 1977).…”
Section: Bst Primary Structurementioning
confidence: 99%